Analisis Butir Soal Bahasa Arab di Madrasah Ibtida’iyyah Bengkulu Tengah Menggunakan Metode Distinguishing, Difficulty, dan Dispersion - Dwi Dinanti, Syintia; Saputa, Prayoga; Aprilia, Risda; Qomari, Nur (Shaut al Arabiyyah, 2024)
This research aims to analyze the questions with a focus on validity, reliability, level of difficulty, distinguishing power, and distractor analysis of the questions. The method used is a quantitative approach by collecting data from the answer sheets of class IV Semester 1 students at MIN 1 Central Bengkulu. The evaluation results showed that of the 25 questions tested, 21 questions were declared valid based on Product Moment analysis, while 4 questions were invalid. Furthermore, of the 25 questions, 21 questions were rated as reliable, while 4 questions were unreliable based on the Cronbach Alpha coefficient. The level of difficulty of the questions shows that most of the questions are at medium difficulty (3 questions) and difficult (22 questions), while there are no questions that are classified as easy. Discriminative power analysis shows that most of the items have good discriminating power. Analysis of question item distractions shows that most of the question items have distractors that are well accepted, but there are some question items that need to be revised. From the results of this evaluation, it was concluded that the evaluation of Arabic language questions at Madrasah Ibtida’iyyah needed to be improved. It is hoped that this evaluation will provide in-depth insight into the weaknesses and potential improvements needed to improve the quality of Arabic language education at MI level.